PELATIHAN FOOTCORE STABILITY PADA ATLET BULUTANGKIS PB SURYANAGA SURABAYA - Khabib, Khabib Abdullah; Cakra Waritsu; Nurul Faj'ri Romadhona; Fandy Ahmad; Ravina Afrianti; Allya Agustinia; Nihaayah Azharoh (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2024)
Badminton is one of the most popular sports in the world, and it has brought significant recognition to Indonesia on the global stage. This sport relies on various physical components, including proper foot placement during movement. Incorrect foot positioning when landing from a jump can increase the risk of ankle injuries. In addition to injuries, this can lead to future balance problems. PB Suryanaga is one of the renowned badminton clubs in Indonesia, producing many talented athletes. The club has numerous athletes training in its dormitory. A crucial type of exercise therapy that is important to implement is footcore stability training, as ankle injury complaints are common among the club's players. This exercise is beneficial for enhancing foot stability and overall balance. After implementing the PKM program, there were significant improvements: athlete knowledge increased from 10% to 100%, skill levels rose from 5% to 85%, static balance improved from 85% to 93%, and dynamic balance increased from 96% to 98%.